Improving Mathematics Learning Outcomes Through the Teams Games Tournament (TGT) Cooperative Learning Model Among Fourth-Grade Elementary School Students - Irda Suriani; Nur Halima Astia; Desi Andini siregar; Aqila Zahra; Fadhila Rifda Siregar; Siti Rahma Siregar; Fatimah Azzarah; Aqila; Nopia Ramadani Tanjung; Alya Syahfitri (Yayasan Citra Dharma Cindekia, 2026)
This study examines the implementation of educational supervision management in improving teacher performance in secondary schools. Employing a qualitative descriptive approach, data were collected through observations, interviews, and document analysis involving school principals, supervisors, and teachers. Findings reveal that systematic supervision—comprising planning, classroom observation, constructive feedback, and follow-up evaluation—significantly enhances teachers’ professional competence, instructional quality, classroom management, and continuous development. Despite challenges such as limited supervisory time, administrative workloads, and varying teacher readiness, effective supervision remains a strategic approach to sustainable school improvement. Strengthening collaboration among school leaders, supervisors, and teachers is essential for maximizing its effectiveness.